THE EFFECT OF BULLYING ON CHILDREN'S PSYCHOLOGICAL DEVELOPMENT - Dewi Rochmawati; Sahening Dian Ardini; Rini Sugiarti; Fendy Suhariadi (Jurnal Impresi Indonesia, 2024)
Bullying is a widely detrimental phenomenon, not only for individual victims but also for society as a whole. This research aims to dig deeper into how bullying affects children's psychological development. Researchers will explore various forms of bullying that may occur in schools and social environments, as well as factors that effect the prevalence and intensity of bullying. The research method used in this journal is descriptive qualitative with a case study design. Researchers used observation and interview techniques to collect data. The data were analyzed by data reduction, data presentation, and conclusion. To ensure the validity of the data, researchers carried out member checks and used triangulation techniques of sources and techniques. This research was conducted at SDTQ AL Abidin Surakarta by taking a sample of several teachers and students as respondents. Research finds that bullying among students is effectd by the family environment, peers and social media, with its impact on children's psychological development. Teachers at SDTQ AL Abidin Surakarta implement effective strategies, including coaching students and involving parents, emphasizing the critical role of teachers in creating a safe learning environment. In conclusion, efforts to overcome bullying in elementary schools require strategies that involve teachers, students and parents to create an environment that supports children's development.